Survei Kemampuan Motorik Peserta Ekstrakurikuler Futsal Di SMK PGRI Kabupaten Rangkasbitung - Lukmanul Hakim; Ahmad Firmansyah; Dodi Nurhidayat (Journal on Education, 2024)
The aim to be achieved in this research is to determine the motor skills of futsal extracurricular participants at SMK PGRI Rangkasbitung Regency. The population in the study were futsal extracurricular participants at SMK PGRI Rangkasbitung Regency, totaling 32 players. The sampling technique used is total sampling where the entire population is used as the research sample. The instruments used in the research were tests and measurements of the Barrow Motor Ability Test which consisted of the standing broad jump, wall pass, zig-zag run, medicine ball put, soft ball throw, and 60 yard dash tests, data analysis techniques used in the research This uses quantitative descriptive analysis techniques with percentages. The results obtained showed that the motor skills of futsal extracurricular participants at SMK PGRI Rangkasbitung Regency were in the "very poor" category at 6.25% (2 students), "poor" at 28.13% (9 students), "fair" at 28 .13% (9 students), "good" 28.13% (9 students), and "very good" 9.38% (3 students).